Medical students' attitudes and wishes towards extending an educational general practice app to be suitable for practice: A cross-sectional survey from Leipzig, Germany. (2nd April 2016) - Sandholzer, Maximilian; Deutsch, Tobias; Frese, Thomas; Winter, Alfred
Abstract: Background: In medical education and practice, smartphone apps are increasingly becoming popular. In general practice, apps could play an important future role in supporting medical education and practice. Objectives: To explore medical students' perceptions regarding the potential of a general practice app for training and subsequent work as a physician. Methods: Cross-sectional survey among Leipzig fourth-year medical students who were provided with an app prototype for a mandatory general practice course. Results: Response rate was 99.3% ( n  = 305/307); 59.0% were female and mean age was 24.5 years. Students certified that the app had a higher potential than textbooks in both education (57.4% vs. 18.0%) and practice (47.1% vs. 22.8%). Students' most desired possible app extensions when anticipating its use for subsequent work as a physician were looking up information for diagnostics, therapy and prediction (85.1%), access to electronic patient files (48.1%), communication and networking (44.3%), organization of medical training (42.9%) and online monitoring of patients (38.1%). Students experienced with medical smartphone apps were more interested in app extensions. Consideration to use the app to support the opening of their own practice was significantly associated with higher interest in accessing electronic patient files, networking with colleagues and telemedicine. Conclusion: Fourth year medical students from Leipzig see a high potential in smartphone apps for education and practice and are interested in further using the technology after undergraduate education.